Has Rural Infrastructure Rehabilitation in Georgia Helped the Poor? - Lokshin, Michael (Published by Oxford University Press on behalf of the World Bank, 2014)
This article proposes a research strategy to deal with the scarcity of data on beneficiaries for conducting impact assessments of community-level projects. Community-level panel data from a regular household survey augmented with a special community module are used to measure the impact of projects. Propensity score-matched difference in-difference comparisons are used to control for time-invariant unobservable factors. This methodology takes into consideration the purposeful placement of projects and their interactions at the community level. This empirical approach is applied to infrastructure rehabilitation projects, for schools, roads, and water supply systems, in rural Georgia between 1998 and 2001. The analysis produces plausible results regarding the size of welfare gains from a particular project at the village level and allows for differentiation of benefits between the poor and the non-poor. The findings of this study can contribute to evaluations of the impact of infrastructure interventions on poverty by bringing new empirical evidence to bear on the welfare and equity implications.